Individualized luteal phase support based on serum progesterone levels in frozen-thawed embryo transfer cycles maximizes reproductive outcomes in a cohort undergoing preimplantation genetic testing - du Boulet, Bertille; Ranisavljevic, Noemie; Mollevi, Caroline; Bringer-Deutsch, Sophie; Brouillet, Sophie; Anahory, Tal (Frontiers in Endocrinology, 2022)
Introduction: Low serum progesterone concentration on frozen embryo transfer (FET) day in hormone replacement therapy (HRT) cycles results in lower reproductive outcomes. Recent studies showed the efficiency of a “rescue protocol'' to restore reproductive outcomes in these patients. Here, we compared reproductive outcomes in HRT FET cycles in women with low serum progesterone levels who received individualized luteal phase support (iLPS) and in women with adequate serum progesterone levels who underwent in vitro fertilization for pre-implantation genetic testing for structural rearrangements or monogenic disorders. Design: This retrospective cohort study included women (18-43 years of age) undergoing HRT FET cycles with pre-implantation genetic testing at Montpellier University Hospital between June 2020 and May 2022. A standard HRT was used: vaginal micronized estradiol (6mg/day) followed by vaginal micronized progesterone (VMP; 800 mg/day). Serum progesterone was measured after four doses of VMP: if <11ng/ml, 25mg/day subcutaneous progesterone or 30mg/day oral dydrogesterone was introduced. Results: 125 HRT FET cycles were performed in 111 patients. Oral/subcutaneous progesterone supplementation concerned 39 cycles (n=20 with subcutaneous progesterone and n=19 with oral dydrogesterone). Clinical and laboratory parameters of the cycles were comparable between groups. The ongoing pregnancy rate (OPR) was 41.03% in the supplemented group and 18.60% in the non-supplemented group (p= 0.008). The biochemical pregnancy rate and miscarriages rate tended to be higher in the non-supplemented group versus the supplemented group: 13.95% versus 5.13% and 38.46% versus 15.79% (p=0.147 and 0.182 respectively). Multivariate logistic regression analysis found that progesterone supplementation was significantly associated with higher OPR (adjusted OR = 3.25, 95% CI [1.38 – 7.68], p=0.007). Conclusion: In HRT FET cycles, progesterone supplementation in patients with serum progesterone concentration <11 ng/mL after four doses of VMP significantly increases the OPR.